‘De meest efficiënte kip ter wereld’. De Nederlandse legkippenfokkerij in de twintigste eeuw - Waaij, Liesbeth; Theunissen, Bert (Studium, 2017)
The most efficient chicken in the world’. Breeding for eggs in the Netherlands in the twentieth centuryThis paper analyses the development of chicken breeding for eggs in the Netherlands in the twentieth century. The Dutch poultry sector was of only marginal significance early in the century, yet after the Second World War it developed into the most industrialised segment of animal husbandry. The introduction of scientific breeding methods played a central role in this, as well as the increasing dominance of specialised commercial breeding companies.While scientists and agricultural engineers developed several innovative approaches to breeding that helped increase egg production significantly, we argue that the methods on which these approaches were based – inbreeding, hybridising, selection and progeny testing – had been used by animal breeders since the eighteenth century. Scientists succeeded in increasing the efficiency of these methods by introducing the quantitative and statistical instruments of quantitative genetics; the new Mendelian theory was of little practical use in this respect. Hybrid breeding methods were also shaped by the commercial interests of breeding companies.In the Netherlands the rise of the poultry industry was slowed down for several decades by the government’s policy to protect the interest of smallholders, yet after the establishment of the EEC this protectionism was dispensed with. As an example of the role of commercial companies we discuss the early history of Hendrix Genetics, a Dutch-based breeding company that is now one of the two multinational enterprises that dominate the breeding market for egg-laying chicken worldwide.